The effect of using simulation interactive Phet on achievement and retention in science for sixth grade primary school girls (Journal of Misan Researches, 2024)
The research aims to know the effect of using simulation interactive Phet on achievement and retention in science for sixth grade primary school students, The researcher used the experimental research method and the experimental design with two independent equal groups, The research was limited to a sample chosen intentionally from sixth grade primary school students, numbering (46) students. The researcher randomly chose Section (A) to be the experimental group and Section (B) to be the control group, with (23) students in each group, The research experiment was conducted by teaching science to the experimental group according to the simulation interactive Phet and to the control group according to the usual method. After the experiment ended, the achievement test prepared by the researcher, which consisted of (30) paragraphs, was applied to the research sample, After two weeks, it was reapplied to the sample to measure retention in science, The data from the two tests were collected and statistical analysis was conducted. The results showed that there was a statistically significant difference at a significance level of (0.05) between the average scores of the experimental group and the average scores of the control group in the achievement test, in favor of the experimental group, There was also a statistically significant difference at a significance level of (0.05) between the average scores of the experimental group and the average scores of the control group in the retention test in science, in favor of the experimental group, In light of the results, the researcher recommended adopting the simulation interactive Phet as a Modern Teaching Strategy, and at the end of the research, suggestions for future research were presented.